PERAN PENDIDIKAN ORANG TUA DALAM MEMBENTUK KARAKTER DAN MOTIVASI BELAJAR ANAK SD - Haryanti; Danik Prahastiwi, Eka (LPPM STAI Muhammadiyah Probolinggo, 2023)
The purpose of this study was to discuss the influence of the family environment on the formation of character and learning behavior of elementary school students. Basically the environment is very influential in shaping a person's attitude and personality, and because each child is a unique person, the family environment also affects the learning behavior of children. If the child is in a good environment, it will have a positive impact on personality development, learning behavior and education. The family environment plays an important role in the formation of personality. The purpose of this study was to clarify the influence of the family environment on the formation of children's personality and learning behavior. This research was conducted through a literature study or literature study, taking into account the results of related journals available in electronic media. Family is the first place for children to learn everything. The family is also a place where children can apply the character values taught in society and taught in schools. The conclusion of this article is as follows: The family environment plays an important role in shaping the personality of students and maintaining basic education through the role of parents and the family environment. A harmonious home environment fully supports the process of personality development and learning behavior of children, thus enabling optimal growth and development of children